Clinton cash the untold story of how and why foreign governments and businesses helped make Bill and Hillary rich - Schweizer, Peter (New York Harper, an imprint of HarperCollinsPublishers, 2015)
In 2000, Bill and Hillary Clinton owed millions of dollars in legal debt. Since then, they?ve earned over
Includes bibliographical references (pages 187-243).
Keywords: Clinton, Bill, 1946---Finance, Personal